THE INFLUENCE OF PRINCIPAL LEADERSHIP, ORGANIZATIONAL CULTURE, AND TEACHER COMPETENCE ON TEACHER PERFORMANCE IN JUNIOR HIGH SCHOOL IN PURWOKERTO DISTRICT - Bagis, Fatmah; Septian Anggara; Hermin Endratno; Totok Haryanto (ITB AAS Indonesia Surakarta, 2025)
This study aims to evaluate how much the influence of school principal leadership, organizational culture, and teacher competence on teacher work performance in the State Junior High School environment in the Purwokerto District area. The research method used was a quantitative approach with a survey technique through the distribution of questionnaires to 190 teacher respondents, who were selected using the convenience sampling method. The data obtained was analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The findings of the study revealed that the leadership of school principals showed a positive and significant relationship to teacher performance. Teacher competence shows a positive and insignificant relationship. Meanwhile, organizational culture shows a negative and insignificant relationship with teacher performance. These results confirm the importance of the strategic role of school principals in encouraging teacher performance improvement through effective leadership. The implications of this study suggest that schools should focus more on strengthening leadership and developing organizational culture and teacher competencies in an integrated and sustainable manner. Keywords: Principal's Leadership, Organizational Culture, Teacher Competence, Teacher Performance